The impossible [videorecording (DVD)] - Sánchez, Sergio G.; Belón, María; McGregor, Ewan, 1971-; Watts, Naomi, 1968-; Holland, Tom, 1996-; Joslin, Samuel; Pendergast, Oaklee; Etura, Marta, 1978-; Möhring, Sönke, 1972-; Chaplin, Geraldine, 1944-; Faura, Óscar; Velázquez, Fernando, 1976- (Summit Entertainment LLC, 2013)
A family on holiday in Thailand is caught in the monstrous tsunami of 2004. Based on a true story.